1979
DOI: 10.1017/s0033583500002754
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides as probes for calcium in biological systems

Abstract: Calcium ion plays an essential role in many biological processes. The environment about Ca2+ may be probed by substitution of tripositive lanthanide ions, Ln3+. Ca2+ proteins fall into two broad classes: those that are inhibited by Ln3+ substitution and those that are not. It is suggested that although Ca2+ undertakes a primarily structural role in the Ln3+ non-inhibited proteins, Ca2+ may be near the active site or participate in the mechanism of action of Ln3+ inhibited proteins. Ca2+ and Ln3+ radii are simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(186 citation statements)
references
References 109 publications
(90 reference statements)
2
183
0
1
Order By: Relevance
“…However, even concentrations as low as 10 μM inhibited crystal formation. Lanthanides are often used to define calcium-binding sites in proteins (38); consequently, samarium was tested as a heavy atom derivative for the structure solution. A samarium-derivatized crystal (MCA2 C213G -Sm) was obtained that revealed a single, fully occupied Sm 3+ -binding site on the surface of the molecule (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, even concentrations as low as 10 μM inhibited crystal formation. Lanthanides are often used to define calcium-binding sites in proteins (38); consequently, samarium was tested as a heavy atom derivative for the structure solution. A samarium-derivatized crystal (MCA2 C213G -Sm) was obtained that revealed a single, fully occupied Sm 3+ -binding site on the surface of the molecule (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies on CaM using techniques such as far-and near-ultraviolet CD measurements, 'H NMR and fluoresence measurements have shown that Tyr-99 and Tyr-138, which are located in domains 111 and IV, are most affected by binding of the first two calciums; this is also consistent with the idea that sites I11 and IV are, in fact, the high-affinity sites for calcium (for review, see [23]). The ability of lanthanides to replace CaZ ' in a variety of proteins arises from the similar ionic size and coordinating properties of these ions [24]. For several calcium binding proteins that bind more than one calcium ion/molecule, it has been shown that terbium binds with the same site preference as calcium (e. g. troponin C [25]).…”
mentioning
confidence: 99%
“…The ability of lanthanides to replace CaZ ' in a variety of proteins arises from the similar ionic size and coordinating properties of these ions [24]. For several calcium binding proteins that bind more than one calcium ion/molecule, it has been shown that terbium binds with the same site preference as calcium (e. g. troponin C [25]).…”
mentioning
confidence: 99%
“…The proposed leaving site for transported protons identified in this work would have been difficult to locate without the use of the positively charged Ho 3þ to reveal a negative patch of residues important for proton unloading. Ho 3þ is a relatively small cation (ionic radii 0.96 Å) with a high charge density and well known to form complexes with the deprotonated form of carboxylates in protein structures (46,47). Our structural and biochemical data identify Ho 3þ as a novel chemical tool for structural identification of proton binding sites.…”
Section: Discussionmentioning
confidence: 87%